Proteomic profiling of HCCAA patients : proteomic analysis of plasma samples from HCCAA patients by 2D-DIGE - Bjarni Oddleifur Einarsson 1994- (2023)
Ritgerðin er lokuð til 01.04.2123 Hereditary Cystatin C Amyloid Angiopathy (HCCAA) is a rare multisystemic inherited disease isolated within the Icelandic population. Evidence indicates it shares pathology with other cerebral amyloid angiopathy (CAA) diseases, such as Alzheimer’s disease (AD). Currently, Arctic Therapeutics is developing the previously approved drug N-acetyl cysteine (NAC), for the treatment of HCCAA as part of a clinical trial and the work herein stems from that ongoing development. The goal was to identify and sequence differentially expressed proteins by 2D-DIGE and tandem mass spectrometry as well as pathway analysis of patients to realize the possible effect of CAA pathology. Patient plasma samples before the drug trial (visit 1/4) were compared to plasma samples at the end of the drug trial (visit 4/4). The analysis of plasma samples from patients in these trials was meant to gauge any detectable difference in the plasma proteome. This was done by established methods of proteomics and the results from this were incremental improvements in the two-dimensional separation of the plasma proteome. Hereditary Cystatin C Amyloid Angiopathy (HCCAA) er sjaldgæfur arfgengur sjúkdómur sem er svæðisbundinn við Ísland. Talið er að hann deili meinafræði með öðrum amýlóíð æðakvillum í heila, líkt og Alzheimers-sjúkdómi. Fyrirtækið Arctic Therapeutics stendur að þróun meðferðar við HCCAA með lyfinu N-asetýlsýstein sem hluti af klínískri rannsókn og kom þetta verkefni til út frá þeirri vinnu. Markmið þessa verkefnis var að bera kennsl á og raðgreina mismunandi tjáð prótein með 2D-DIGE og raðmassagreiningu til þess að sjá hugsanleg áhrif CAA meinafræðinnar. Samanburður var gerður á blóðvökvasýnum greindra HCCAA sjúklinga fyrir og eftir lyfjatöku með viðurkenndum próteinmengjaaðferðum til þess að bera kennsl á breytingar í próteinmengi blóðvökva. Helstu niðurstöður verkefnisins voru framþróun á tvívíðri aðgreiningu blóðvökvapróteina sem nýtist í áframhaldandi greiningarvinnu fyrirtækisins. Verkefnið ...